2017
DOI: 10.7150/ijms.18706
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Dehydroepiandrosterone on Improving Mitochondrial Function and Reducing Apoptosis of Cumulus Cells in Poor Ovarian Responders

Abstract: Poor ovarian responders (PORs) pose a great challenge for in vitro fertilization (IVF). Previous studies have suggested that dehydroepiandrosterone (DHEA) may improve IVF outcomes in PORs. The current study attempted to investigate the clinical benefits of DHEA in PORs and the possible mechanisms of DHEA on cumulus cells (CCs). This was a prospective study performed at one tertiary center from January 2015 to March 2016. A total of 131 women who underwent IVF treatment participated, including 59 normal ovarian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 45 publications
(70 reference statements)
0
34
0
Order By: Relevance
“…On the other hand, a loss of androgen actions, as in ARKO models, leads to elevated levels of follicular atresia, evident by the presence of pyknotic granulosa cells and degenerate oocytes (Hu et al 2004, Shiina et al 2006, Walters et al 2007. Clinical evidence supporting this mechanism come from the findings from one study that compared to normal ovarian responders, POR patients supplemented with DHEA were reported to produce a greater number of top-quality embryos on day 3 and increased fertilization rates, and their cumulus cells displayed reduced DNA damage and expression of apoptosis-related genes (Lin et al 2017). Similarly in another study, cumulus cells collected before and after DHEA treatment in women with POR displayed an increase in the ratio of BCL2 (anti-apoptotic) to BAX (pro-apoptotic) (Tsui et al 2014).…”
Section: Current Implications and Future Directions From Basic Researmentioning
confidence: 99%
“…On the other hand, a loss of androgen actions, as in ARKO models, leads to elevated levels of follicular atresia, evident by the presence of pyknotic granulosa cells and degenerate oocytes (Hu et al 2004, Shiina et al 2006, Walters et al 2007. Clinical evidence supporting this mechanism come from the findings from one study that compared to normal ovarian responders, POR patients supplemented with DHEA were reported to produce a greater number of top-quality embryos on day 3 and increased fertilization rates, and their cumulus cells displayed reduced DNA damage and expression of apoptosis-related genes (Lin et al 2017). Similarly in another study, cumulus cells collected before and after DHEA treatment in women with POR displayed an increase in the ratio of BCL2 (anti-apoptotic) to BAX (pro-apoptotic) (Tsui et al 2014).…”
Section: Current Implications and Future Directions From Basic Researmentioning
confidence: 99%
“…However, direct action of DHEA on the target organs has been proposed [ 42 , 43 ] but is still inconclusive. Regarding the molecular mechanism, our previous studies revealed that DHEA supplementation could improve mitochondrial function and reduce apoptosis in the cumulus cells [ 44 ] and human granulosa cell line [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to observe that some studies have shown that DHEA supplementation for IVF in women with decreased ovarian reserve did not increase the clinical rate of pregnancy. It is therefore noted that the mechanism of action of this steroid hormone remains obscure and that there are several controversies about it [28][29][30][31][33][34][35].…”
Section: Therapeutic Effects Of Dhea Supplementation In Patients Withmentioning
confidence: 99%